Improving Students' Responsibilities in Thematic Learning Through the Development of PjBL Model-Based Student Worksheets - Zaitun Zaitun; Pargito Pargito; Mohammad Mona Adha; Dwi Yulianti (BIRCU, 2023)
The problem in this study is that students do not show a responsible attitude towards the learning activities they participate in, this is due to the absence of LKPD development to increase students' responsible attitude. The purpose of this research is to produce valid, practical, and effective project-based learning worksheets to improve students' responsible attitudes. The sampling technique was cluster random sampling, namely 28 students in class IVA at SD Negeri 3 Gedung (as an experimental class), and 30 students in class IVA at SD Negeri 3 Bumirestu (as a control class). Data collection techniques using test techniques, questionnaires and documentation. Test the hypothesis in this study using the independent t test technique.